Antenatal Care Skills Education for Diploma 3 Midwifery Study Program STIKes Bhakti Pertiwi Indonesia - Albahra Albahra; Rosmiati Rosmiati; Partono Siswosuharjo (Akademi Keperawatan RSPAD Gatot Soebroto, 2022)
This study aims to provide education on Antenatal Care skills to increase Antenatal Care test scores for fifth semester students of the Diploma-3 Midwifery Study Program at STIKes Bhakti Pertiwi Indonesia. This study uses a type of correlation study with a retrospective approach (Retrospective Study). The population in this study were all students of the Diploma III Midwifery Study Program in the fifth semester who had taken the Antenatal Care exam and received a skill target of 100 students. The sampling technique uses total sampling. Bivariate data processing using Spearman Rank. Achievement of skill targets averaged 39 targets, of which there were at most 11-20 female students getting 60-80 varney targets and the rest getting 81-100 varney reports. Most of the antenatal care test scores were 75-80, namely 67S, 67%. The conclusion is that there is no statistically significant relationship between the target of antenatal care skills and the score of the antenatal care test (p = 0.058; p) 0.05) (p = (0.05).